2005
DOI: 10.1029/2002rg000122
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency variability of the large‐scale ocean circulation: A dynamical systems approach

Abstract: Citation: Dijkstra, H. A., and M. Ghil (2005), Low-frequency variability of the large-scale ocean circulation: A dynamical systems approach, Rev. Geophys., 43, RG3002,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
264
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 235 publications
(271 citation statements)
references
References 247 publications
(492 reference statements)
5
264
2
Order By: Relevance
“…We are then back, in a pullback setting, to the notion of local attractors that compose the global attractor and that can be of topologically very different natures. In the autonomous context, such coexistence of topologically distinct local attractors is well known in the climate sciences (Ghil and Childress 1987;Dijkstra and Ghil 2005;Simonnet et al 2005Simonnet et al , 2009, and references therein), while it is also observed in the numerical results of Figs. 5 and 6 herein for the present ocean model.…”
Section: B Interpretationmentioning
confidence: 55%
See 1 more Smart Citation
“…We are then back, in a pullback setting, to the notion of local attractors that compose the global attractor and that can be of topologically very different natures. In the autonomous context, such coexistence of topologically distinct local attractors is well known in the climate sciences (Ghil and Childress 1987;Dijkstra and Ghil 2005;Simonnet et al 2005Simonnet et al , 2009, and references therein), while it is also observed in the numerical results of Figs. 5 and 6 herein for the present ocean model.…”
Section: B Interpretationmentioning
confidence: 55%
“…Again as usual, these questions require one to climb the rungs of a hierarchy of successively more complex and detailed climate models (Ghil 2001;Dijkstra and Ghil 2005;, and references therein). Naturally, introducing noise in the forcing may substantially modify the system's behavior: a random dynamical system extension of the present study is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative explanations identified oceanic nonlinearity as a possible source of the oscillatory behavior (Jiang et al 1995;Cessi 2000;Dewar 2001;Dijkstra and Ghil 2005;Simonnet et al 2006). Dewar (2001), in particular, argued for a key role of intrinsic oceanic, eddy-driven variability in controling the spectral content of the coupled system at decadal and longer time scales.…”
Section: Introductionmentioning
confidence: 99%
“…The DDS analogs are conservative (e.g., Hamiltonian) dynamical systems [28,29] versus forced-dissipative systems (e.g., the well-known Lorenz system [30]). Typical examples of conservative systems occur in celestial mechanics [31,32], while dissipative systems are often used in modeling geophysical [33,34] and many other natural phenomena.…”
Section: Classification Of Bdesmentioning
confidence: 99%